Stratified scaffolds for osteochondral tissue engineering - Nooeaid, Patcharakamon; Schulze-Tanzil, Gundula; Boccaccini, Aldo R. (Cartilage Tissue Engineering, 2015)
Stratified scaffolds are promising devices finding application in the field of osteochondral tissue engineering. In this scaffold type, different biomaterials are chosen to fulfill specific features required to mimic the complex osteochondral tissue interface, including cartilage, interlayer tissue, and subchondral bone. Here, the biomaterials and fabrication methods currently used to manufacture stratified multilayered scaffolds as well as cell seeding techniques for their characterization are presented
Keywords: Alginate; Biomaterial; Mesenchymal stem cells; Osteochondral tissue engineering; Stratified scaffold